El circuito asistencial de la fibrilación auricular en pacientes ambulatorios: estudio observacional Audit fibrilación auricular en el Baix Ebre - Giménez-García, Emmanuel (Aten Primaria, 2014)
AIM: To provide insights into the characteristics and management of outpatients when their atrial fibrillation (AF) was first detected: diagnosis, treatment and follow-up in the context of the public health system. DESIGN: AFABE is an observational, multicentre descriptive study with retrospective data collection relating to the practice patterns, management and initial strategies of treatment of patients with diagnosed AF in the context of primary care, emergency and cardiologists of the public health system. SETTING: Primary and Specialist care. Baix Ebre region. Tarragona. Spain. SUBJECTS: A representative sample of 182 subjects > 60-year-old with AF who have been randomized, recruited among the registered patients with AF in 22 primary care centres in the area of the study. MESUREMENTS: Demographic data, comorbidities (AF), CHA2DS2-VASc and HAS_BLED scores, and practice patterns results between Primary Care and referral services. RESULTS: A total of 182 patients were included (mean age 78.5 SD:7.3 years; 50% women). Most patients (68.3% 95%CI; 60.3-76.3) had the first contact in Primary Care, of which 56.3% (95%CI; 45.2-66.0) were sent to Hospital Emergency Department where 72.7% (95%CI: 63.5-79.0) of the oral anticoagulation and 58.4% (95%CI: 49.4-66.9) of antiarrhytmic treatments were started. More than half (55.9%:95%CI; 47.2-64.7, of patients with permanent AF were followed-up by the Cardiology department. CONCLUSIONS: Most patients with newly diagnosed AF made a first contact with Primary Care, but around half were sent to Hospital Emergency departments, where they were treated with an antiarrhythmic and/or oral anticoagulation.